1991
DOI: 10.1099/0022-1317-72-2-349
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus heterogeneity during an epidemic: analysis by limited nucleotide sequencing (SH gene) and restriction mapping (N gene)

Abstract: The genes encoding the small hydrophobic (SH) proteins of a series of respiratory syncytial (RS) virus strains were amplified using the polymerase chain reaction, cloned and sequenced. Analysis of the SH gene sequences from 12 RS virus strains isolated between 1956 and 1989 confirmed the homogeneity of the two subgroups, A and B, previously defined serologically. Although there is only 76% deduced amino acid sequence identity of SH proteins between subgroups, there was little variation in deduced amino acid se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
81
1
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(89 citation statements)
references
References 28 publications
5
81
1
2
Order By: Relevance
“…Studies on successive epidemics at a single location have reported that several genotypes co-circulate during each epidemic, the proportion of which vary, and that the genotypes which predominate in one epidemic tend to become less significant in the next epidemic. 9,11,19,20 We are unable to determine if specific treatment for RSV affected outcome. Only 15 of 26 patients received anti-RSV therapy, with 10 of 15 receiving ribavirin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on successive epidemics at a single location have reported that several genotypes co-circulate during each epidemic, the proportion of which vary, and that the genotypes which predominate in one epidemic tend to become less significant in the next epidemic. 9,11,19,20 We are unable to determine if specific treatment for RSV affected outcome. Only 15 of 26 patients received anti-RSV therapy, with 10 of 15 receiving ribavirin.…”
Section: Discussionmentioning
confidence: 99%
“…Restriction enzyme mapping of the N gene has allowed the classification of RSV isolates into six (NP1-NP6) genotypes. 9 Sequence analysis of the SH gene has been used to further subdivide subgroup A RSV isolates into four genotypes (SHL 1,3,4; SHL2; SHL5 and SHL6). G gene sequence variability has been shown to be closely related to these SHL genotypes and restriction enzyme mapping of the G gene can be used to assign subgroup A isolates to the SHL lineages.…”
mentioning
confidence: 99%
“…Briefly, total RNA was extracted from whole-lung tissue and then cDNA was synthesized. Primers specific for the nucleocapsid (N) gene of RSV were used (forward, 5=-GGAACAAGTTGTT GAGGTTTATGAATATGC-3=; reverse, 5=-CTTCTGCTGTCAAGTCTA GTACACTGTAGT-3=) (2). The viral loads in each sample were calculated by relative quantification.…”
Section: Mice and Virusmentioning
confidence: 99%
“…Respiratory syncytial virus (RSV) encodes 11 proteins, 3 of which are transmembrane surface glycoproteins found in the viral envelope: the G (glycoprotein) (18,40), F (fusion) (11), and SH (small hydrophobic) (7,12) proteins. The G protein is a type II transmembrane protein, with an N-terminal transmembrane domain.…”
mentioning
confidence: 99%